2017
DOI: 10.1007/978-3-319-70178-3_24
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Androgen Regulation of Metabolism in Nonhuman Primates

Abstract: The in-depth characterization of sex differences relevant to human physiology requires the judicious use of a variety of animal models and human clinical data. Nonhuman primates (NHPs) represent an important experimental system that bridges rodent studies and clinical investigations. NHP studies have been especially useful in understanding the role of sex hormones in development and metabolism and also allow the elucidation of the effects of pertinent dietary influences on physiology pertinent to disease state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 82 publications
0
15
0
Order By: Relevance
“…In peripubertal T onset females, diminished basal lipolysis in both SC and visceral abdominal fat depots co-occurs with augmented insulin-mediated FFA uptake into visceral adipocytes, alone, contributing to enlarged visceral, but not SC, adipocytes [162]. Since adrenergic (sympathetic nervous system noradrenalin) stimulation of lipolysis is also diminished only in SC adipocytes, unaffected adrenergic stimulation of lipolysis in enlarged visceral adipocytes likely contributes increased lipid release into the liver, with subsequent adiposity-associated insulin resistance and compensatory hyperinsulinemia [162]. T + WSD female macaques thus demonstrate the need for the onset of both hyperandrogenism and high fat diet during adolescence to evoke the adult metabolic derangements engaged by early-to-mid gestation T exposure, alone (models #8 vs. #3, respectively, Figure 1).…”
Section: Metabolic Pcos-related Traits In Macaque Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…In peripubertal T onset females, diminished basal lipolysis in both SC and visceral abdominal fat depots co-occurs with augmented insulin-mediated FFA uptake into visceral adipocytes, alone, contributing to enlarged visceral, but not SC, adipocytes [162]. Since adrenergic (sympathetic nervous system noradrenalin) stimulation of lipolysis is also diminished only in SC adipocytes, unaffected adrenergic stimulation of lipolysis in enlarged visceral adipocytes likely contributes increased lipid release into the liver, with subsequent adiposity-associated insulin resistance and compensatory hyperinsulinemia [162]. T + WSD female macaques thus demonstrate the need for the onset of both hyperandrogenism and high fat diet during adolescence to evoke the adult metabolic derangements engaged by early-to-mid gestation T exposure, alone (models #8 vs. #3, respectively, Figure 1).…”
Section: Metabolic Pcos-related Traits In Macaque Modelsmentioning
confidence: 99%
“…Partially emulating the metabolic outcomes of early-to-mid gestation T-exposure, female macaques exposed to peripubertal onset of T, and supplemented with a high fat diet (T + WSD), demonstrate increased abdominal 'android' fat and abdominal circumference indicative of increased visceral adiposity [132]. In peripubertal T onset females, diminished basal lipolysis in both SC and visceral abdominal fat depots co-occurs with augmented insulin-mediated FFA uptake into visceral adipocytes, alone, contributing to enlarged visceral, but not SC, adipocytes [162]. Since adrenergic (sympathetic nervous system noradrenalin) stimulation of lipolysis is also diminished only in SC adipocytes, unaffected adrenergic stimulation of lipolysis in enlarged visceral adipocytes likely contributes increased lipid release into the liver, with subsequent adiposity-associated insulin resistance and compensatory hyperinsulinemia [162].…”
Section: Metabolic Pcos-related Traits In Macaque Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, the present study advances our understanding of the functional and transcriptional response in SC-WAT associated with dynamic changes in fat mass in response to diet-induced obesity and weight loss and expands our previous studies in NHPs [17,18,20,[64][65][66]. Our study has several limitations.…”
Section: Discussionmentioning
confidence: 63%
“…Sex hormones, such as estrogen and androgen, contribute to the sex differences in body weight and metabolism between males and females and are thought to be responsible for sex-specific differences (Ogawa et al, 2015;Boese et al, 2017;True et al, 2017). Multiple studies have shown that estrogen prevented cell death in many cell types (Kanda and Watanabe, 2003;Kim et al, 2006;Vasconsuelo et al, 2008;Bailey et al, 2012).…”
Section: Introductionmentioning
confidence: 99%